Stable isotope evidence of human diet in Mediterranean context during the Last Glacial Maximum. Issue 154 (May 2021) - Drucker, Dorothée G.; Naito, Yuichi I.; Coromina, Neus; Rufí, Isaac; Soler, Narcís; Soler, Joaquim
Abstract: The Final Gravettian in Europe overlapped with the cold and dry climatic event of Heinrich 2 (ca. 27–23.5 kyr cal BP), which caused the contraction of human distribution over refuge regions in the southern peninsulas of Europe. Here, we consider the human subsistence in the northeast Iberian Peninsula, where an extensive range of small to large prey was available. Four human remains from the Serinyà caves were investigated using the stable isotope ratios of carbon, nitrogen, and sulfur of bulk collagen ( δ 13 Ccoll, δ 15 Ncoll, δ 34 Scoll ) and of phenylalanine and glutamine amino acids ( δ 15 NPhe, δ 15 NGlu ). Direct AMS dating of the human and animal remains from the Final Gravettian levels of Mollet III, Reclau Viver, and Arbreda at Serinyà confirmed their chronological position from 27.5 to 22.6 kyr cal BP and the occurrence of four different human individuals. The δ 13 Ccoll and δ 15 Ncoll values showed a large contribution of terrestrial prey to the dietary protein of the individuals. The δ 34 Scoll values were consistent with a subsistence based on the local continental resources, without detectable contribution of marine resource. The δ 15 NPhe and δ 15 NGlu values confirm that freshwater resources were not a substantial component of the diet of the considered individuals. Contrast in the isotopic amounts in bulk collagen could be interpreted as the result of different proportions of terrestrial prey in human diet at Serinyà. Altogether, the isotopic investigation reveals the importance of terrestrial over aquatic resources in the subsistence of the studied Final Gravettian individuals from the Serinyà caves in northeastern Iberia during the Last Glacial Maximum. It would be consistent with a scenario of a productive enough terrestrial ecosystem to sustain hunter-gatherer subsistence in this refuge region.